New insights into roles of IL-7R gene as a diagnostic biomarker for post-stroke depression - Liu, Mengyu; Sun, Haochen; Yao, Qun; Wang, Duohao; Zhang, Jihong; Ye, Xing; Qi, Xinyang (Frontiers in Immunology, 2024)
BackgroundPost-stroke depression (PSD) is the most prevalent neuropsychiatric complication following a stroke. The inflammatory theory suggests that PSD may be associated with an overactive inflammatory response. However, research findings regarding inflammation-related indicators in PSD remain inconsistent and elusive. This study aimed to screen the diagnostic markers that helps to distinguish between PSD and post-stroke non-depressed (PSND) patients.MethodsTwo GEO datasets, including patients with major depression disease (MDD) and controls (CON, GSE98793), ischemic stroke (IS) and CON (GSE16561), were used to analyzed differentially expressed genes (DEGs) and perform enrichment analysis. Protein-protein interaction (PPI) network and Random Forest analysis were used to screen the candidate hub genes. CIBERSORT was performed to analyze the immune infiltration. We analyzed the proteins that interact with the hub genes using string database, circRNA-miRNA-mRNA ceRNA network of the hub genes using RNAInter, miRWalk, miRDB and Starbase databases, and the drugs that regulate the hub genes by DSigDB database. We further verified the expression of the hub genes using Quantitative Real-Time PCR from the blood of patients and CON.ResultsFrom the screened 394 DEGs, the DEGs were found primarily related to activation of immune response. PPI network and random forest analysis obtained the hub genes: IL-7R. ROC analysis showed that IL-7R had a good diagnostic and predictive effect on MDD and IS patients. The proportions of macrophages M0 and monocytes in patients were significantly higher than those in CON. We constructed PPI network and ceRNA network that related to IL-7R. The perturbagen signatures and computational drug signatures were found that can target IL-7R. The expression of IL-7R in MDD, PSND and PSD patients was lower than that in CON, and the expression of IL-7R in PSD patients was lower than that in PSND patients.ConclusionThese findings indicate that IL-7R may serve as a diagnostic marker to distinguish between PSD and PSND patients, and targeting IL-7R as a therapeutic target could potentially improve treatment outcomes for PSD.